Viewpoints on humans in the philosophy of Confucianism and lessons for Vietnam today - Dang, Thi Phuong Anh (Horizonte, 2021)
Human position in society was one of the critical topics that attracted philosophers' attention in ancient China. Confucianism had systematic views on the human's role and position in social stabilization. The article aims to analyze the essential characteristics of the viewpoint on humans in Confucianism's philosophy before the Qin dynasty, such as the unity between politics and morality, the humanity in the promotion of moral rule, human civilization. These views still have influences on upholding culture as the spiritual foundation of today's Vietnamese society. This study used a qualitative research methodology through deriving from the literature and examinations of secondary resources to find out these influences. Research results show that Vietnam today is taking the people's legitimate interests and aspirations as a premise for building national solidarity, developing education and training for the development of the knowledge economy, and a lesson about focusing on people's livelihood. Although there are limitations of the times, such as discrimination of caste and status, fate, and human nature are subject to a priori idealism, the philosophy of Confucianism still has specific Vietnamese values in the current society.